Collaborative concession in food movement networks: the uneven relations of resource mobilization - Sbicca, Joshua, author; Luxton, India, author; Hale, James, author; Roeser, Kassandra, author; MDPI AG, Basel, Switzerland, publisher (Colorado State University. Libraries, 2019)
How do food movements prioritize and work to accomplish their varied and often conflicting social change goals at the city scale? Our study investigates the Denver food movement with a mixed methods social network analysis to understand how organizations navigate differences in power and influence vis-à-vis resource exchange. We refer to this uneven process with the analytical concept of "collaborative concession". The strategic resource mobilization of money, land, and labor operates through certain collaborative niches, which constitute the priorities of the movement. Among these are poverty alleviation and local food production, which are facilitated by powerful development, education, and health organizations. Therefore, food movement networks do not offer organizations equal opportunity to carry out their priorities. Concession suggests that organizations need to lose something to gain something. Paradoxically, collaboration can produce a resource gain. Our findings provide new insights into the uneven process by which food movement organizations-and city-wide food movements overall-mobilize.
Keywords: movement; alternative food; local food; social network analysis; social movements; resource mobilization; mixed methods; alliance building